KESANTUNAN BERBAHASA DALAM INTERAKSI SOSIAL SISWA KELAS XI DI PONDOK TAHFIDZ PESANTREN UMMUL QURRA’ KENDARI - Jihan Fahirah; La Ode Balawa; sulfiah (Jurnal Bastra (Bahasa dan Sastra), 2026)
The purpose of this study is to describe the forms of politeness maxims in the social interactions of eleventh-grade students at Pondok Tahfidz Pesantren Ummul Qurra’ Kendari. This research is a field study, and the method used is a descriptive method aimed at providing a detailed and in-depth description of the research findings. The data used in this study consists of students' utterances during social interactions in the environment of Pondok Tahfidz Pesantren Ummul Qurra’ Kendari, specifically in speech situations. Data collection methods include observation and conversation techniques, while data collection techniques consist of recording and note-taking. The data analysis technique employed is a sociopragmatic approach, involving stages such as data transcription, data classification, data interpretation, and data analysis. The research findings indicate that the language politeness at Pondok Tahfidz Pesantren Ummul Qurra' Kendari applies six politeness maxims: (1) the tact maxim, (2) the generosity maxim, (3) the approbation maxim, (4) the modesty maxim, (5) the agreement maxim, and (6) the sympathy maxim. These maxims are evident in the students' interactions and reflect the application of politeness principles in the pesantren environment.